Girassol Transport and Logistics - Business Plan for a Company Start-up in Angola - Bravo da Rosa, V (2014)
This business plan is for a company start-up of a transport and logistics company that initially offers a selected range of transportation services in and around the city of Luanda. Evidently, it is very hard, if not impossible, to raise a large amount of capital for an enterprise start-up through bank loans; hence the following proposal for private investment has been elaborated. Bank loans require numerous guarantees, which private investors don’t, but in addition private investment has other benefits that actively support and monitor a new business start-up, which will be of great help, as this is the first the proposed management team ventures into establishing its own business. In the first semester of 2010, private investment in Angola reached an impressive 1255 million US Dollars, beating by far the same period in 2009, which attracted investments of 450 million US Dollars, as explained by Aguinaldo Jaime of ANIP (National Agency of Private Investment in Angola) in OJE (2011) and illustrates that this emerging and fast evolving market is an attractive target for private investors. The following report details company background, market and competitor analysis, as well as the business, marketing, and financial plans to give potential private investors an insight into the Angolan economy and the potential return with the start-up of a small transport and logistics company in Luanda, Angola. An in-depth market analysis of the Angolan market proved rather difficult as not much written and trusted information can be researched from a distance. In order to present realistic facts in this business plan research had to be conducted locally. This start-up would be managed by two professionals that were educated and worked many years in Europe, but also have the cultural knowledge to make it a success in Angola. The combination of European and African work ethics and strategies is a valuable asset for the success of this enterprise. The required investment for the proposed business is $785.000, main costs being the purchase of a small vehicle fleet and operational, personnel and administration costs for the first three months. After this initial period the business will be financing itself and starting to bring in profits. The potential EBIT for the first year sums up to $1.569.600, which would guarantee a big profit for the business and an excellent rate of return for the investor. This is a fantastic opportunity as much for the investor as for the entrepreneur and would also constitute an excellent example of the economical change happening in a fast emerging market in Africa.